Legal Study on the Role of Law in Guaranteeing Freedom of Religion Based on the Principles of Pancasila - Zidan Alif Priadi A; Niandari, Tia (International Journal of Sustainable Law, 2025)
Freedom of religion is one of the fundamental human rights guaranteed by the Indonesian constitution, specifically Article 28E paragraphs (1) and (2) and Article 29 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. This guarantee is inseparable from the philosophical foundation of Pancasila, which places Belief in One God as the first principle and serves as an umbrella for diversity of beliefs in Indonesia. This paper aims to analyze the role of law in ensuring the implementation of freedom of religion in accordance with the values of Pancasila. The research method used is normative juridical, with a legislative and conceptual approach, as well as a literature study from various scientific journals and legal documents. The results of the study show that positive law in Indonesia has provided a strong framework for protecting freedom of religion, but in practice it still faces various challenges, such as biased interpretations, horizontal conflicts, and discrimination. The role of law is not only limited to regulation, but also to consistent enforcement and public education to foster tolerance and mutual understanding. The integration of Pancasila values in every policy and law enforcement is crucial to creating a harmonious society that upholds religious pluralism